Znaczenie i rola rynku międzybankowego w finansowaniu działalności banku hipotecznego - Półtorak, Bogusław (The Role of the Inter-Bank Market in the Financing of the Mortgage Bank, 2005)
This paper presents ways, conditions, mechanism and development of inter-bank market as a source of Polish mortgage bank financing. The author analyses deposits of non-financial institutions as a source of Polish mortgage bank, too. Next he compares those two ways. Development of the inter-bank market in Poland depends on the activities of the commercial banks. The commercial banks may gain a lot in this area. In this paper the author tries to identify and point out the main factors that will participate in the change and increase of the role of inter-bank market in financing of Polish mortgage banks.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (3); 2005; nr 1062, s. 142-150